Case Report: Clinical effect of combining auricular cartilage, full-thickness auricular skin graft, and local flap from the right nasal ala in complex nasal defect reconstruction - Zuo, Jinfu; Wang, Rong; Fan, Xiaoting; Zhang, Haixia; Zhai, Zhaohui; Sun, Huachang (Frontiers in Surgery, 2024)
The aim of this report was to evaluate the efficacy of nasal reconstruction using auricular cartilage combined with auricular full-thickness skin graft and a local flap from the right nasal ala for correcting complex nasal defects, and its impact on the patient's quality of life and psychological well-being. We present the case of a 50-year-old female with a severe nasal deformity due to a car accident, characterized by a missing right alar flap and an exposed right nostril. The patient underwent nasal reconstructive surgery using auricular cartilage combined with an auricular full-thickness skin graft and a local flap from the right nasal ala. Detailed records of the patient's postoperative recovery, surgical outcomes, and satisfaction were made at follow-up. The survival rate of the grafted skin and flaps on the nasal ala, septum, and dorsum was high. The reconstructed right nasal ala closely resembled the left, and the patient was very satisfied. In patients with complex nasal deformities, nasal reconstruction using ear cartilage combined with auricular full-thickness skin grafts and local flaps can achieve satisfactory aesthetic and functional outcomes. The high level of postoperative satisfaction suggests that this technique significantly improves patients’ quality of life and psychological well-being.